2023
DOI: 10.3389/fimmu.2023.1160719
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the role of STAT3 in macrophage polarization

Abstract: The physiological processes of cell growth, proliferation, differentiation, and apoptosis are closely related to STAT3, and it has been demonstrated that aberrant STAT3 expression has an impact on the onset and progression of a number of inflammatory immunological disorders, fibrotic diseases, and malignancies. In order to produce the necessary biological effects, macrophages (M0) can be polarized into pro-inflammatory (M1) and anti-inflammatory (M2) types in response to various microenvironmental stimuli. STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 124 publications
4
19
0
Order By: Relevance
“…While it is necessary to consider that macrophages are an extremely plastic cell population and the membrane-bound markers and cytokines assessed here are not sufficient to affirm a bona-fide complete engagement of macrophages into a permanent well-defined sub-type, our results suggest that IL-6 (4 CH) could contribute to the promotion of an M2a-like phenotype. These results could be in accordance with the fact that IL-6 is known to trigger STAT3 signaling [ 51 ], and that the latter has been reported to be involved in M2a polarization [ 52 ]. Interestingly enough, Fernando et al have already documented that, when combined with IL-4 and IL-13, IL-6 enhanced the polarization of alternatively activated macrophages, based on their increased expression of arginase-1, Ym1, and CD206 [ 53 ].…”
Section: Discussionsupporting
confidence: 87%
“…While it is necessary to consider that macrophages are an extremely plastic cell population and the membrane-bound markers and cytokines assessed here are not sufficient to affirm a bona-fide complete engagement of macrophages into a permanent well-defined sub-type, our results suggest that IL-6 (4 CH) could contribute to the promotion of an M2a-like phenotype. These results could be in accordance with the fact that IL-6 is known to trigger STAT3 signaling [ 51 ], and that the latter has been reported to be involved in M2a polarization [ 52 ]. Interestingly enough, Fernando et al have already documented that, when combined with IL-4 and IL-13, IL-6 enhanced the polarization of alternatively activated macrophages, based on their increased expression of arginase-1, Ym1, and CD206 [ 53 ].…”
Section: Discussionsupporting
confidence: 87%
“…Alveolar macrophages are considered a therapeutic target because they are poised to rapidly release large amounts of inflammatory cytokines in response to LPS [24]. Several studies have shown that suppressing alveolar macrophage STAT3 phosphorylation, thereby reducing the production of pro-inflammatory cytokine, such as IL-6, TNF-α, IL-1β, a cytokine known to be involved in the pathogenesis of inflammatory lung disease [25]. In our study, we showed that lung injury score was significantly reduced by Niclosamide administration in LPS-induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…STATs are crucial transcription factors in macrophage polarization, with STAT1 being integral to M1, and STAT3/6 to M2 polarization. [ 145 ]. In cervical cancer, FGD5-AS1, via the miR-129-5p/bone marrow stromal cell antigen 2 (BST2) axis, promotes tumor growth and M2 polarization [ 146 ].…”
Section: Lncrnas That Modulate Macrophage Nf-κb Activity In Cancermentioning
confidence: 99%